Single-step isolation of carbon nanotubes with narrow-band light emission characteristics - Turek, Edyta (Sci Rep, 2019)
Lack of necessary degree of control over carbon nanotube (CNT) structure has remained a major impediment factor for making significant advances using this material since it was discovered. Recently, a wide range of promising sorting methods emerged as an antidote to this problem, all of which unfortunately have a multistep nature. Here we report that desired type of CNTs can be targeted and isolated in a single step using modified aqueous two-phase extraction. We achieve this by introducing hydration modulating agents, which are able to tune the arrangement of surfactants on their surface, and hence make selected CNTs highly hydrophobic or hydrophilic. This allows for separation of minor chiral species from the CNT mixture with up to 99.7 ± 0.02% selectivity without the need to carry out any unnecessary iterations. Interestingly, our strategy is also able to enrich the optical emission from CNTs under selected conditions.